Yakuza [videorecording] (The Inside Story host & producer, Loren Legarda, 1990)
Operations of Yakuza, a mafia oriented organization that drives at illegal activities ranging from prostitution to drugs; Options of the Aquino government in determining the faith of the military bases in the country; Profile of Manoling Morato during his term as chairman of the MTRCB.